Sinuskurven überall: Zur Mathematik der Panorama-Fotografie (mathematica didactica, 2021)
Panorama fotos (often providing 360°-pictures) yield extremal distortions which irritate the viewer. Instead of the expected straight lines one is confronted with a multitude of curved bows. In the article we show that these are partial sine curves. Such sine curves (with identical frequency, but arbitrary amplitude and arbitrary phase shift) are essential for our visual perception: The usual obsession with the stiff view described by the central perspective hides this phenomenon. With a little training one realizes the ubiquity of such sinecurves. Altogether we are going to describe part of the mathematical (and nonmathematical) background of panorama fotografy.